Patients' and family caregivers' understanding of the cancer stage, treatment goal, and chance of cure: A study with patient‐caregiver‐physician triad. Issue 1 (13th July 2017) - Shin, Dong Wook; Cho, Juhee; Kim, So Young; Yang, Hyung Kook; Park, Keeho; Kweon, Sun‐Seog; Koh, Dai Ha; Nam, Hae‐Sung; Park, Jong‐Hyock
Abstract: Objective: Accurate understanding of the extent of disease, treatment goal, and prognosis is a prerequisite for patients with cancer and their caregivers to make informed decision. We sought to evaluate patients' and family caregivers' understanding of the cancer stage, treatment goal, and chance of cure taking their own physician's evaluation as reference. Methods: A national survey was performed with 750 patient‐caregiver dyads (75.5% participation rate) recruited by 134 oncologists in 13 cancer centers (93% participation rate) in South Korea. Both patients and caregivers were asked to report their knowledge of patient's cancer stage, treatment goal, and chance of cure. Concordance was evaluated with percentage agreement and weighted κ, and predictors of discordance of patient and caregiver's response with that of physician's were explored by multivariate regression analyses with mixed effect model. Results: The agreement rates between patient‐physician and caregiver‐physician were 63.0% and 65.9% for disease stage, 69.0% and 70.0% for treatment goal, and 41.4% and 45.1% for chance of cure. When discordance occurs, patients and caregivers often had an optimistic view. Distant stage, older age, female sex, and absence of depression were associated with optimistic view of patients, and there was significant between‐physician variance for all 3 outcomes. Conclusion: The discordance revealed that our study suggests the need for better communication between physician and patients, as well as the caregivers. Research is needed to develop a comprehensive strategy to improve the understanding of the patients and family so that treatment decisions are made based on realistic estimation.